Depeche mode Jacob Taubes between politics, philosophy, and religion - Kopp-Oberstebrink, Herbert 1960- (Brill, 2022)
"The philosopher and ordained rabbi Jacob Taubes (1923-1987) is one of the most important figures on the 20th century German intellectual scene and beyond. As one of the first academic jet-setters, he had been the holder of the founding chair for Jewish Studies at Freie Universität Berlin and was professor at Columbia University. Taubes combined traditional Jewish thinking with contemporary issues in philosophy such as theories of secularization, the relation between politics and religion, and the hermeneutics of time, more specifically messianism, apocalyptic thinking, and gnosticism"--
Keywords: Taubes, Jacob -- 1923-1987; Taubes, Jacob; Jewish philosophers / Germany / Biography; Jewish philosophers / United States / Biography; Jewish philosophers; Germany; United States; Biographies; Konferenzschrift -- 2017 -- Zürich